TRADISI MENGEMIS DI TEMPAT WISATA RELIGI - Supraptingsih, Umi (JURNAL KARSA (Terakreditasi No. 80/DIKTI/Kep/2012), 2012)
Umi Supraptingsih (Penulis, dosen STAIN Pamekasan, Jl. Raya Panglegur Km. 04 Pamekasan)     Abstract The act of begging of beggar appears tradition for generations and it becomes inheritant profession. Social and  economic characteristics of beggar are influenced by several factors---natural and human resources. Places of beggar to do begging, Api Tak Kunjung Padam (eternal flame) and Batu Ampar, are distinctive. The former is the common tourism spot, but the later is the religous tourism place. The factors cause the begging are the natural setting condition that does not support the  beggar to earn sufficient income, the low level of education, inedequate parenting pattern, less religious teaching comprehension, the extinct of abahsment, and instant needs.  Establishing an actual cultural  communication and asking the participation of stake holders---philantropist, academician, public figure, religious scholar, and government, will hopefully decrease the number of beggar. Kata-kata kunci tradisi, mengemis, dan kebutuhan hidup